REFLECTION ELEMENTS OF DEMOCRACY BY THE EXAMPLE OF THE ETHNONYM EPIC «MANAS» (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
By analyzing the various aspects of relations between the ethnonyms of the epic «Manas», are examples of symptoms and the development of democracy in the life of the Kyrgyz people. It is shown that the Kyrgyz people have always tried to live by respecting the dignity of their own and other people (ethnonyms), to build relationships with others based on mutual respect and good neighborliness.
Keywords: the epic “Manas”, ethnonym, democracy